On Becoming a Leader - Warren Bennis (Philadelphia Basic Books, 2021)
Deemed "the dean of leadership gurus" by Forbes magazine, Warren Bennis has for years persuasively argued that leaders are not born-they are made. Delving into the qualities that define leadership, the people who exemplify it, and the strategies that anyone can apply to achieve it, his classic work On Becoming a Leader has served as a source of essential insight for countless readers. In a world increasingly defined by turbulence and uncertainty, the call to leadership is more urgent than ever.Featuring a provocative new introduction, this new edition will inspire a fresh generation of potential leaders to excellence.
Keywords: Leadership; Business; Nonfiction; Management; Self Help; Personal Development; Entrepreneurship; Education; Psychology; (HRM3045-N) Strategic Management and Responsible Leadership